2023
DOI: 10.3389/fendo.2023.1291774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS-CoV-2 infection on hypothyroidism and subclinical hypothyroidism: a meta-analysis

Jiaqi Wei,
Fenghua Zhang

Abstract: BackgroundIn recent years, the outbreak of COVID-19 caused by SARS-CoV-2 has been witnessed globally. However, the impact of SARS-CoV-2 infection on thyroid dysfunction and subclinical thyroid dysfunction remains unclear. Therefore, this meta-analysis aimed to assess the effects of SARS-CoV-2 infection on thyroid dysfunction and its relationship with the severity of COVID-19.MethodsWe systematically searched databases including PubMed, Willey Library, Embase, Web of Science, CNKI, Wanfang, and VIP. We focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A meta-analysis encompassing 565 samples from 6 studies revealed that the severe COVID-19 group exhibited significantly lower TSH and FT3 levels compared to the mild group. However, no significant differences were observed in FT4 levels between the groups ( 15 ). The variations in FT4 levels observed in our study can be attributed to a more detailed classification of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 86%
“…A meta-analysis encompassing 565 samples from 6 studies revealed that the severe COVID-19 group exhibited significantly lower TSH and FT3 levels compared to the mild group. However, no significant differences were observed in FT4 levels between the groups ( 15 ). The variations in FT4 levels observed in our study can be attributed to a more detailed classification of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 86%